Afghanistan : HIPC Initiative Paper. (IMF Staff Country Reports; Country Report ;, 2010)
This report examines the Heavily-Indebted Poor Countries (HIPC) Initiative paper on Afghanistan. Afghanistan has made sufficient progress in meeting the completion point triggers, despite a challenging environment during the HIPC interim period, marked by increasing insecurity in parts of the country and the global fuel and food crisis. It has fully implemented the triggers on preparing and implementing a poverty reduction strategy paper, maintaining a stable macroeconomic environment, improving debt management and public financial and expenditure management, and improving the business environment.